2016
DOI: 10.1016/j.midw.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Influences of prior miscarriage and weight status on perinatal psychological well-being, exercise motivation and behavior

Abstract: Objectives women who have experienced miscarriage may be at increased risk for elevated depressive and anxiety symptoms in subsequent pregnancies. Exercise may be a useful strategy for coping with these symptoms. Little is known about how miscarriage influences prenatal exercise behavior. The study purpose was to examine the influences of miscarriage history and prepregnancy weight status on pregnant women’s psychological health, exercise motivation, and behavior using the Theory of Planned Behavior. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Moreover, postpartum women who experienced several complications during pregnancy were more likely to report postpartum PTSD and to report a negative experience of labor and delivery. This result is in line with other studies that have found an association between medical-obstetric dimensions of pregnancy and the subjective experience of childbirth as well as postpartum mental health (Devlin et al, 2016;Fenaroli et al, 2016Fenaroli et al, , 2019Furtado et al, 2018). Finally, women whose partners had not been present during delivery were more likely to experience both postpartum anxiety symptoms (state and trait) and PTSD thus underling the importance of (intra-partum and postpartum) partners' support in preventing postpartum psychological distress (Collins et al, 1993;Hodnett, 2002;Hodnett et al, 2011;Michels et al, 2013;Tani and Castagna, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, postpartum women who experienced several complications during pregnancy were more likely to report postpartum PTSD and to report a negative experience of labor and delivery. This result is in line with other studies that have found an association between medical-obstetric dimensions of pregnancy and the subjective experience of childbirth as well as postpartum mental health (Devlin et al, 2016;Fenaroli et al, 2016Fenaroli et al, , 2019Furtado et al, 2018). Finally, women whose partners had not been present during delivery were more likely to experience both postpartum anxiety symptoms (state and trait) and PTSD thus underling the importance of (intra-partum and postpartum) partners' support in preventing postpartum psychological distress (Collins et al, 1993;Hodnett, 2002;Hodnett et al, 2011;Michels et al, 2013;Tani and Castagna, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…as well as a variety of medical-obstetric variables prior to and during pregnancy (e.g., previous miscarriages, high risk pregnancy, etc.) have been found to impact on pregnant women's mental health (e.g., Devlin et al, 2016;Furtado et al, 2018). Again, a personal history of mental illness prior to pregnancy has been reported to increase the risk of developing a psychological disorder during pregnancy, thus underling the continuity of psychological disorders (Cox et al, 2014;Biaggi et al, 2016).…”
Section: Psychological Well-being Of Expectant Mothersmentioning
confidence: 99%
“…Where the Wald test was statistically significant (alpha < 0.05 level after Benjamini-Hochberg false discovery rate correction [31]), we conducted pairwise tests to find statistically different pairs. All analyses were adjusted for factors identified as being predictive of physical activity in prior literature: race/ethnicity, age, history of miscarriage, number of jobs (0, ≥1), marital status (married/living together, unmarried), education (<high school, high school, some college, bachelor's degree, advanced degree), parity, and BMI (13,(17)(18)(19)29,32,33).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, research has suggested that pregnant women with different pre-pregnancy body mass index (BMI) status and parity have different behaviors and views regarding weight management issues during pregnancy. 18,19 These different contexts of maternal characteristics might have effects on the cognition of pregnant women. In that, we will also consider the moderating effects of pre-pregnancy BMI status and parity.…”
Section: Purposementioning
confidence: 99%